Study the effects of creativity-based lesson study on the teachers' professional skills and creative manner of students and teachers - bahman hurizad (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2010)
In a quasi-experimental study, the effect of lesson study with emphasis on creativity was investigated on creativity of 78 teachers and 1900 primary school pupils. Getting involved teachers and pupils in explorative activities and projects in real life, in order to develop their creativity, valuing creativity and providing a rich and supportive environment, have been among enrichment program. The staff was trained for 68 hours, within the year with lesson study and using the methods of developed creativity, enriched the curriculums of school. Based on the creativity test scores of pupils and teachers, the experimental group compared with the control group, showed a significant increase, and between the teachers' creativity scores and the average score of their pupils a positive and significant linear correlation exists. In addition, the lesson study caused the growth of teachers’ professional skills